A Case Study Of A Deformation Mechanism Around A Two-Entry Gate-Road System Involving Probable Time-Dependent Behavior - M. K. Larson (International Conference on Ground Control in Mining, 1995)
The U.S. Bureau of Mines and Cyprus Shoshone Coal Corp. conducted a study of deformation mechanisms around a longwall gate-road system in an underground coal mine. Of particular interest was roof deformation over the headgate entry. The strata above and below the coal seam are very weak, carbonaceous mudstones that have planes of weakness oriented along the bedding. Visual observations of previous gate roads over several years suggested that deformation was time dependent and resulted in creep along joints or crack growth. Instruments were installed at a test site to measure deformation around the entry, strew changes in the pillar, and loads transferred to support systems. Multipoint extensometers, instrumented bolts, instrumented trusses, biaxial stressmeters, borehole pressure cells, and single-point extensometers were installed. Monitoring continued until the longwall face passed the test site by 38.7 m (127 ft). Results show that fracture zones arched over the entry from both ribs, most bolts and trusses were loaded past their yield point, and the largest change in secondary principal stress was almost horizontal in the pillar. Displacement measurements in the roof showed classic primary creep.